Implementasi Manajemen Berorientasi Mutu Pada STAI Tebing Tinggi Deli - wandi, Suwandi; Asrul Nasution; Ismal MZ; Suwastati Sagala (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2023)
quality and quality of higher education. Higher Education Quality is carried out by implementing quality assurance activities with the PDCA model, namely: 1) Plan (Planning), 2) Do (Implementation), 3) Check (Examination) and 4) Action (Action). By applying the quality assurance model, the quality management of the High Quality Regulation can be monitored both planning, processes, outputs and outcomes. This type of research uses qualitative research, namely research that uses data analysis, which is information or information obtained based on informants, This is in line with the opinion of Bogdan and Taylor, that qualitative research is a research process that produces descriptive data in the form of written or oral words from people (informants) and observed behaviors (based on interviews, and documentation). Data collection techniques use techniques whose relevance is related to qualitative research (in terms of documentation, and interviews). Meanwhile, data analysis techniques are carried out to see the extent of the picture and facts that can be contained in the research results. Based on the results of the study, it was obtained that the implementation of quality-oriented management at STAI Tebing Tinggi Deli can be seen from the following aspects, curriculum aspects, special service aspects, facilities and infrastructure aspects, partnership aspects. Based on the conditions at STAI Tebing Tinggi Deli, an internal institution is needed that functions to carry out quality assurance for the implementation of activities. With the running of internal quality assurance, it is hoped that the quality majamen service process will be of high quality in the future.